2020
DOI: 10.1101/2020.12.07.414227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-autophagy role of Atg5 and NBR1 in unconventional secretion of IL-12 prevents gut dysbiosis and inflammation

Abstract: Intestinal myeloid cells play a critical role in balancing intestinal homeostasis and inflammation. Here, we report that expression of the autophagy related 5 (Atg5) protein in myeloid cells prevents dysbiosis and excessive intestinal inflammation by limiting IL-12 production. Mice with a selective genetic deletion of Atg5 in myeloid cells (Atg5ΔMye) showed signs of dysbiosis prior to colitis and exhibited severe intestinal inflammation upon colitis induction that was characterized by increased IFNγ production… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 130 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…Intestinal macrophages exhibit an anti-in ammatory phenotype under homeostatic conditions that allows them to function as highly phagocytic and bactericidal cells without initiating an in ammatory response (Bain and Schridde, 2018). A functional autophagic pathway in macrophages is critical for this anti-in ammatory phenotype (Lee et al, 2016;Merkley et al, 2020;Zhang et al, 2017). It is suggested that anti-in ammatory macrophages rely mainly on mitochondrial metabolism such as the oxidative phosphorylation (OXPHOS) and fatty acid oxidation for energy production (Diskin and Palsson-McDermott, 2018;Shanmugam et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal macrophages exhibit an anti-in ammatory phenotype under homeostatic conditions that allows them to function as highly phagocytic and bactericidal cells without initiating an in ammatory response (Bain and Schridde, 2018). A functional autophagic pathway in macrophages is critical for this anti-in ammatory phenotype (Lee et al, 2016;Merkley et al, 2020;Zhang et al, 2017). It is suggested that anti-in ammatory macrophages rely mainly on mitochondrial metabolism such as the oxidative phosphorylation (OXPHOS) and fatty acid oxidation for energy production (Diskin and Palsson-McDermott, 2018;Shanmugam et al, 2003).…”
Section: Introductionmentioning
confidence: 99%